Standard opioid-containing versus opioid-sparing anesthesia on early postoperative recovery after video-assisted thoracic surgery: A propensity-weighted analysis - Jiang, Yan-yu; Li, Zhen-ping; Yao, Ming; Zhou, Qing-he (Frontiers in Surgery, 2022)
Background: Opioids have several side effects. At present, there is no large sample clinical study on the effects of opioid-sparing anaesthesia on early postoperative recovery after thoracoscopic surgery. This study was to investigate the effects of opioid-sparing anaesthesia on early postoperative recovery after thoracoscopic surgery. Methods: Adult patients who underwent video-assisted thoracic surgery from 1 January 2019 to 28 February 2021 were enrolled by reviewing the electronic medical records. Participants were divided into opioid-sparing anaesthesia (OSA group) and opioid-containing anaesthesia (STD group) based on the intraoperative opioid usage. The propensity-score analysis was to compare the early postoperative recovery between two groups. The outcome measurements included the incidence of postoperative nausea and vomiting (PONV) during entire hospital stay, need for rescue antiemetic medication, postoperative-pain episodes within 48 h after surgery, need for rescue analgesia 48 h postoperatively, duration of postoperative hospital stay, length of PACU stay, postoperative fever, postoperative shivering, postoperative atrial fibrillation, postoperative pulmonary infection, postoperative hypoalbuminaemia, postoperative hypoxaemia, intraoperative blood loss, and intraoperative urine output. Results: A total of 1975 patients were identified. No significant difference was observed in patient characteristics between the OSA and STD groups after adjusting for propensity score-based inverse probability treatment weighting. The incidence of postoperative nausea and vomiting was significantly lower in the OSA group than in the STD group (14.7% vs.18.9%, p=0.041). The rescue antiemetic use rate was lower in the OSA group than in the STD group (7.5% vs.12.2%; p=0.002). PACU duration was longer in the OSA group than in the STD group (70.8 ± 29.0 min vs. 67.3 ± 22.7 min; p = 0.016). The incidence of postoperative fever was higher in the STD group than that in the OSA group (11.0% vs.7.7%; p=0.032). There were no differences between the groups in terms of other outcomes. Conclusions: Our results suggest that opioid-sparing anaesthesia has a lower incidence of postoperative complications than opioid-based anaesthetic techniques.